2018
DOI: 10.1038/s41598-018-21842-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial reduction in sealed caries lesions is strain- and material-specific

Abstract: Sealing can arrest caries lesions. We aimed to evaluate if sealing effects and kinetics are bacterial-strain and sealing-material specific. Human dentin discs were mounted in a dual-chamber device. Caries lesions were induced chemically and contaminated with either Lactobacillus rhamnosus (LR) or Streptococcus sobrinus (SS). For (1) kinetics assessment, the initial bacterial load and the sealing period were varied, and lesions sealed using a self-etch adhesive and composite. For (2) comparing materials, six se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Our study confirms findings from in vivo studies, which demonstrated long-term survival of sealed bacteria [10,11]. Strain-specific survival was also demonstrated in vitro recently [12].…”
Section: Discussionsupporting
confidence: 91%
“…Our study confirms findings from in vivo studies, which demonstrated long-term survival of sealed bacteria [10,11]. Strain-specific survival was also demonstrated in vitro recently [12].…”
Section: Discussionsupporting
confidence: 91%
“…The significant antibacterial efficacy of SRF-CPC is most likely related to the sustained release of the CPC from the SRF, in addition to the high sensitivity of E. faecalis to CPC [17]. Furthermore, the sealing of the dentinal tubules by the SRF might have caused additional environmental stress to bacteria residing deep inside the tubules [33]. An intimate relation between the SRF and the root canal walls was confirmed using SEM.…”
Section: Discussionmentioning
confidence: 99%
“…From previous investigations it is known, however, that bacteria can be found within enamel lesions at an early stage of caries development, even with lesions revealing macroscopically intact surfaces [63]. Since bacteria control of deeper intralesional aspects has not been investigated up to now, at best, some positive indirect conclusions by analogy from studies referring to sealing of occlusal caries would seem permissible [64], and this would suggest that it is not necessary to remove all carious dentin prior to placing the restoration; over time, sealing of carious dentin obviously will result in lower (time-and material-specific [65]) levels of infection if compared to the traditional concepts aiming at complete dentin caries removal [66]. Certainly, additional research to elucidate the fate of microorganisms hemmed by the external resin infiltration of proximal lesions is required.…”
Section: Discussionmentioning
confidence: 99%